The EFFECT OF DIFFERENT MULCHING TYPES ON THE WEED OF SEA BUCKTHORN: EFFECT OF DIFFERENT MULCHING TYPES ON THE WEED OF SEA BUCKTHORN - Jigjidsuren, Otgon (International Journal For Research In Agricultural And Food Science, 2023)
This study was conducted in order to determine how the use of organic (straw, sawdust) and inorganic (Polyethylene, woven fabric) mulches affect weed species composition and weed seed bank in sea buckthorn field. The number and species composition of weeds in the years of the study differed significantly depending on the mulching types. In spring and May, polyethylene and woven fabric versions completely suppressed weeds, while control-2, which didn’t fight weeds, had more weeds growing by 34-203 per/m2 in 2021 and 56-192 per/m2 in 2022. The yield of one bush was 2939.4 g in the version with woven fabric version, which was 336.1-2714.1 g more than the other versions. fruit yield had a strong negative correlation with the number of weeds P=0.77, and weed biomass had a weak negative correlation with fruit yield P=0.5. 40-69.3 % of weed seed bank in the soil were contained in the 0-10 cm deep stratum and decreased from spring to autumn. Weed seed bank were reduced by 1.1-2.6 times in the mulched versions compared to control 2, and increased by 1.3 times in control 2. In statistical processing, the mulched versions differed significantly in weed seed bank.